Penguatan Kapasitas Kelembagaan Badan Usaha Milik Nagari Bukit Gadang Mandiri dalam Pengelolaan Sumber Kekayaan Nagari - Jumiati Jumiati; Boni Saputra; Lince Magriasti; Dwi Finna Syolendra (Universitas Lancang Kuning, 2022)
This community service partner is the State-Owned Enterprise (BUMNag) Bukit Gadang Mandiri Nagari Sikabau, Dharmasraya Regency. This service activity was carried out to contribute ideas and counseling about the institutional strengthening of BUMNag Bukit Gadang Mandiri in the Management of Wealth Resources of Nagari Sikabau, Dharmasraya Regency. BUMNag is a pillar of economic activity in Nagari which functions as a social institution and commercial institution to be able to encourage the economy of Nagari, with the hope of prospering the economy of the Nagari community. The methods and approaches used include education, socialization, training, and mentoring